Elektrokonvülsif tedaviye bağlı hemodinamik cevabı önlemede esmololün iki farklı dozunun karşılaştırılması - (:unkn) unknown (My University, 2010)
Amaç: Elektrokonvülsif tedavi (EKT) esnasındaki sempatik deşarj nedeniyle ciddi taşikardi ve ani hipertansiyon gelişmesi, başta serebrovasküler ve koroner problemler olmak üzere birçok sistem üzerine olumsuz etki oluşturacağından, hastalarda hemodinamiyi stabil tutmak oldukça önemlidir. Kısa süreli bir işlem olan EKT’de kullanılacak ilaçlar da kısa etki süreli ve hızlı derlenme özellikleri taşımalı, aynı zamanda nöbet süresini etkilememelidir. Çalışmamızda EKT esnasında oluşan hemodinamik cevabı önleyebilmek için kısa etki süreli bir beta adrenerjik blokör olan esmololün iki farklı dozunu karşılaştırmayı amaçladık. Gereç ve Yöntem: Çalışma 18 -65 yaş arası, en az dört seans EKT uygulanacak ASA 1-3 risk grubundaki 26 olguya uygulanacak toplam 104 EKT seansında planlandı. Hastaların ilk EKT seansında çalışma ilacı uygulanmadan önceki ölçümleri ve değerlendirmesi yapılarak çalışma grubuna alınıp alınamayacağı belirlendi. Elektroensefalografi (EEG) ve Elektromyelografi (EMG) elektrodları bağlandı. Sağ dirsek üstüne tansiyon aleti manşonu bağlandı ve anestezi indüksiyonunun hemen öncesinde radiyel arter atımının hissedilemediği en az basınca kadar şişirildi. Anestezi indüksiyonunun hemen sonrasında çalışma ilacı olarak; %0.9 sodyum klorür, 0.5 mg/kg esmolol ve 1 mg/kg esmolol randomize olarak uygulandı. Uygulamacı hangi ilacı verdiğini bilmeden ölçümleri yaparak kaydetti. Plasebo olarak %0.9 sodyum klorür verilene başlangıç, 0.5 mg/kg esmolol verilene ölçüm I ve 1 mg/kg esmolol verilene ölçüm II adı verildi. EKT Thymatron system 4 bipolar EKT cihazı ile uygulandı. Nöbet aktivitelerinin takibinde hem EEG kayıtları, hem EMG kayıtları, hem de manşon bağlanan ekstremitedeki kasılma süresinin kronometre ile ölçülen kayıtları tutuldu. Hastaların çalışma ilacı verilmeden evvel (bazal), EKT sonrası 1., 5., 10. ve 15. dakikalarda elektrokardiyografi (EKG), pulse oksimetre ve PETAŞ KMA 265 R cihazı ile monitörize edilerek periferik oksijen satürasyonu (SpO2), sistolik (SAB), diastolik (DAB), ortalama arter basıncı (OAB) ve kalp hızı (KH) değerleri ve EKT sonrasındaki maksimum nabızları kaydedildi. Bulgular: Çalışmada 20 olguya uygulanan 60 EKT seansı değerlendirmeye alındı, 6 hasta çalışma dışı bırakıldı. Olguların ortalama yaşı 31.75±3.71, vücud ağırlıkları 71.65±5.3 kg ve akım şiddeti 19.0±6.19’dur. Hastaların SAB, DAB, OAB ve KH’ları bazal ölçümleri arasında anlamlı bir fark bulunamadı. 1. ve 5. dakikalarda her üç ölçüm arasında fark- bulundu, 10. dakikada ise Başlangıç ile Ölçüm I ve II arasında fark bulunmasına karşın ölçüm I ve II arasında fark yoktu. 15. dakikada tüm ölçümler arasında farklılık bulunmadı. Maksimum kalp atım hızı ölçümleri arasındaki ikili karşılaştırmalarda Başlangıç’a göre Ölçüm I’de ve Ölçüm II’de, Ölçüm I’e göre Ölçüm II’de görülen düşüş ileri düzeyde anlamlı bulundu. Nöbet süreleri arasındaki fark ise her üç ölçüm arasında da istatistiksel olarak anlamlı bulunmadı.

Objective: Because of tachycardia and sudden hypertension due to sympathetic discharge during electroconvulsive therapy (ECT), negative effects on many systems particularly cerebrovascular and coronary problems could occur. Hence it is very important to keep patients in stable hemodynamic status. Drugs used during ECT, which is a brief procedure, must have short half lives and fast metabolism features, but also should not effect seizure duration. In our study we aimed to compare the effect of two different doses of beta adrenergic blocker esmolol, which has a short half life, in preventing hemodynamic response. Material and Methods: The study has been planned as total of 104 ECT sessions on 26 patients in ages between 18 and 65 years and at least four sessions of ECT planned for each patient in ASA 1-3 risk group. The patients were decided to be included in or excluded from the study based on measurements obtained during first ECT session. Electroencephalographs (EEG) and Electromyelography (EMG) electrodes were connected. Blood pressure cuff was placed above the right elbow and it was inflated up to the least pressure needed to stop radial artery pulse just before anesthesia induction. Immediately after anesthesia induction; 0.9% sodium chloride, 0.5 mg/kg esmolol, or 1 mg/kg esmolol were randomly adminestered. The anesthesia team recorded the measurements without knowing which drug was given. The measurements of placebo (0.9% sodium chloride) recipients were named (Beginning).The measurements of 0.5 mg/kg esmolol and 1 mg/kg esmolol recipients were respectively called (Measurement I) and (Measurement II). ECT was delivered with ECT Thymatron system 4 bipolar machine. In monitoring seizure activities both EEG and EMG recordings, and also contraction time in BP cuff connected extremity recorded by stopwatch, were used. The measurements were recorded before giving medication (basal) and after ECT on 1st, 5th, 10th and 15th minutes. Electrocardiograph (ECG), pulse oxymetry, and PETAfi KMA 265 R were monitored. Also peripheral oxygen saturation (SpO2), systolic (SAB), diastolic (DAB), mean artery pressure (OAB) and heart rate (KH) values and post-ECT maximum heart rate were recorded. Results: In this study 60 ECT sessions conducted on 20 patients were included, 6 patients were excluded. The average age of patients were 31.75±3.71; average body weight and electric current power were 71.65±5.3kg and 19.0±6.19, respectively. SAB, DAB, OAB and KH basal measurements were not significantly different. The 1st and 5th minute measurements showed significant difference among all 3 groups. There were significant differences between Beginning and Measurment I and Beginnning and Measurement II at 10th minute recordings, but no significant difference between Measurements I and II. The 15th minute measurements demonstrated no significant difference among all 3 groups. When dual comparisons of maximum heart rate measurements were conducted, strongly significant decreases were found in Measurement I and II according to Beginning and in Measurement II according to Measurement I. The differences between seizure durations among all three groups were not statistically significant. Conclusions: Esmolol 1 mg/kg dose kept hemodynamic response more stable than esmolol 0.5 mg/kg dose during ECT. No side effects were observed at both doses and no effects on seizure duration were detected. Based on this study, to prevent hemodynamic response in the process of ECT, a treatment plan must be done and 1 mg/kg esmolol might be a good choice.
Comparison of two different dosages of esmolol in the prevention of hemodynamic response due to electroconvulsive therapy
Keywords: Anestezi